2018
DOI: 10.1534/genetics.118.301456
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Epigenetic Inheritance Is Negatively Regulated by the HERI-1 Chromodomain Protein

Abstract: Transgenerational epigenetic inheritance (TEI) is the inheritance of epigenetic information for two or more generations. In most cases, TEI is limited to a small number of generations (two to three). The short-term nature of TEI could be set by innate biochemical limitations to TEI or by genetically encoded systems that actively limit TEI. In Caenorhabditis elegans, double-stranded RNA (dsRNA)-mediated gene silencing [RNAi (RNA interference)] can be inherited (termed RNAi inheritance or RNA-directed TEI). To i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 60 publications
(114 reference statements)
0
56
0
Order By: Relevance
“…4d, Extended Data Fig. 10e), albeit to a much lesser extent than reported in previous cases 40,41 . Similarly, removal of the endonuclease ERI-1 42 weakly increased the persistence of silencing (Extended Data Fig.…”
mentioning
confidence: 55%
“…4d, Extended Data Fig. 10e), albeit to a much lesser extent than reported in previous cases 40,41 . Similarly, removal of the endonuclease ERI-1 42 weakly increased the persistence of silencing (Extended Data Fig.…”
mentioning
confidence: 55%
“…CD, chromo domain; CSD, chromo shadow domain; ChIP, chromatin immunoprecipitation; in vitro, in vitro peptide binding assay; co-IP, co-immunoprecipitation; Tg, transgene; DB, DELTA-BLAST. ‡ HPL-1, HPL-2: (Couteau et al, 2002;Schott et al, 2006;Koester-Eiserfunke and Fischle, 2011;Studencka et al, 2012a,b;Towbin et al, 2012;Garrigues et al, 2015;Vandamme et al, 2015;McMurchy et al, 2017); CEC-1: (Agostoni et al, 1996;Saltzman et al, 2018); CEC-3: (Greer et al, 2014); CEC-4: (Gonzalez-Sandoval et al, 2015); CEC-6: (Saltzman et al, 2018); HERI-1: (Perales et al, 2018); MRG-1: (Takasaki et al, 2007;Cabianca et al, 2019;Hajduskova et al, 2019).…”
Section: Chromo Domain Proteins and Spatial Organization Of The Genomementioning
confidence: 99%
“…In a genetic screen for factors that prolong the transgenerational retention of RNAi inheritance, a recent study characterized the chromo domain protein HERI-1 (heritable enhancer of RNAi; formerly known as CEC-9) (Perales et al, 2018). Interestingly, ChIP assays revealed recruitment of HERI-1 to genes undergoing nuclear RNAi; this recruitment is dependent on HRDE-1 and SET-32 (also known as HRDE-3), a methyltransferase contributing to H3K9 methylation and nuclear RNAi inheritance.…”
Section: Germline Immortality and Transgenerational Epigenetic Inherimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that selection enables maintenance of heritable RNAi indefinitely (>80 generations) [10]. Control over the duration of transgenerational silencing is achieved via an elaborate regulatory pathway [8], and disabling some of the genes in the pathway (for example, met-2, which encodes for an H3K9 methyltransferase) leads to stable inheritance [14,25,26]. Currently, the source of variability in the inheritance capacity of genetically identical individuals is completely unaccounted for.…”
mentioning
confidence: 99%